Ethnic patriotism and the East African revival: a history of dissent, c. 1935 - 1972 - Peterson, Derek R. (African studies, 2013)
"Ethnic Patriotism and the East African Revival shows how, in the era of African political independence, cosmopolitan Christian converts struggled with east Africa's patriots over the definition of culture and community. The book traces the history of the East African Revival, an evangelical movement that spread through much of eastern and central Africa. Its converts offered a subversive reading of culture, disavowing their compatriots and disregarding their obligations to kin. They earned the ire of east Africa's patriots, who worked to root people in place as inheritors of ancestral wisdom. This book casts religious conversion in a new light: not as an inward reorientation of belief, but as a political action that opened up novel paths of self-narration and unsettled the inventions of tradition"--